Solid solution formation in Cu/Co ultrathin film systems - Protsenko, I.Yu.; Cheshko, I.V.; Javorsky, J. (Functional Materials, 2006)
The β-(Co-Cu) fcc solid solution (SS) in multilayer Cu/Co nanocrystalline films (layer number 2 to 8) at ultra-small individual layer thickness (maх. 10 nm) has been studied. The electrophysical properties (resistivity and temperature resistance coefficient) of the film alloys,the correlation thereof with the layer number, the total effective thicknessand thecomponent concentrations have been established. Изучены условия формирования твердого раствора β-(Co-Cu) в многослойных нанокристаллических пленках (число слоев от 2 до 8) на основе CО и Cu с ультрамалой эффективной толщиной отдельных слоев (не более 10 нм). Исследованы электрофизические свойства (удельное сопротивление и ТКС) пленочных сплавов, установлена их корреляция с числом слоев, общей эффективной толщиной и концентрацией компонент. Вивчено умови формування твердого розчину β-(Co-Cu) у багатошарових нанокристалiчних плiвках (кiлькiсть шарiв вiд 2 до 8) на основi CО та Cu з ультрамалою товщиною окремих шарiв (не бiльше 10 нм). Дослiджено електрофiзичнi властивостi (питомий опiр та ТКО) плiвкових сплавiв, встановлено їх кореляцiю з кiлькiстю шарiв, загальною ефективною товщиною та концентрацiєю компонент.